PENINGKATAN KEMAMPUAN BACA TULIS PEGON DI SDN WONOSALAM 5 JOMBANG - Sugiyanto Sugiyanto; Nurul Indana; Lailatul Maskhuroh; Misbachul Umam (ISLAMIDA Journal of Islamic Studies, 2023)
Diniyah education is a branch of science that applies classical or modern teaching and attempts to instill Islam as part of the foundation of life for students to produce famous 'ulama' who not only understand science, but also have broad religious insight and horizons of thought as a form of problem solving. in society. In this research, researchers used qualitative research methods. Meanwhile, the data collection methods used are: 1) Observation, 2) Interviews, 3) Documentation. Data is analyzed by reducing irrelevant data, explaining the data and drawing research conclusions. The results of this research are: 1. Everyone has abilities but with different capacities. There are those who understand faster by writing pegon, there are also those who read it first. 2. Effort is an endeavor (to achieve a goal, solve a problem, find a way out, etc.). Likewise, what the Mulok Diniyah teacher at SDN Wonosalam 5 Jombang does is carry out according to the existing curriculum, given various motivations and learning techniques. 3. Supporting and inhibiting factors. Supporting factors are a. Facilities/infrastructure, b. Government and school institution support, c. Motivation, d. Family support. Inhibiting factors are: a. Psychological differences, b. Lack of knowledge of hijaiyah letters, c. Lack of discipline